2018
DOI: 10.1016/j.cub.2018.01.070
|View full text |Cite
|
Sign up to set email alerts
|

Precise Motor Control Enables Rapid Flexibility in Vocal Behavior of Marmoset Monkeys

Abstract: Investigating the evolution of human speech is difficult and controversial because human speech surpasses nonhuman primate vocal communication in scope and flexibility [1-3]. Monkey vocalizations have been assumed to be largely innate, highly affective, and stereotyped for over 50 years [4, 5]. Recently, this perception has dramatically changed. Current studies have revealed distinct learning mechanisms during vocal development [6-8] and vocal flexibility, allowing monkeys to cognitively control when [9, 10], … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 38 publications
3
66
0
Order By: Relevance
“…In a 235 previous study, we demonstrated that marmosets interrupt their vocalizations shortly after 236 noise onset when perturbation starts after vocal onset [18], supporting the idea that these 237 animals tend to avoid calling in ambient noise. Such call interruptions, however, were rare 238 (2.6% of all calls), indicating stark neuronal and/or anatomical constraints in exhibiting such 239 behavior [18] and resulting in a large fraction of phee calls being perturbed by noise bursts. 240…”
Section: Monkeys 190mentioning
confidence: 55%
See 4 more Smart Citations
“…In a 235 previous study, we demonstrated that marmosets interrupt their vocalizations shortly after 236 noise onset when perturbation starts after vocal onset [18], supporting the idea that these 237 animals tend to avoid calling in ambient noise. Such call interruptions, however, were rare 238 (2.6% of all calls), indicating stark neuronal and/or anatomical constraints in exhibiting such 239 behavior [18] and resulting in a large fraction of phee calls being perturbed by noise bursts. 240…”
Section: Monkeys 190mentioning
confidence: 55%
“…Based on the current work and earlier studies [14,18], we propose a hypothetical neuronal 251 model suggesting various audio-vocal control mechanism involving cortical, subcortical, and 252 corticofugal connections capable of modulating vocal behavior in a noisy environment (Fig. 253 4).…”
Section: Mechanisms Counteracting Involuntary Audio-vocal Effects Neementioning
confidence: 83%
See 3 more Smart Citations